Determination of content, cooking loss, and bioaccessibility of thiamine in red meats using in vitro simulated human gastrointestinal digestion system - Demir, Kübra; Ertekin Tezcan, Elanur; Uğur, Halime; Yaman, Mustafa; Çatak, Jale; Yaman, Mustafa; Çatak, Jale; Demir, Kübra (Plapiqui, 2023)
Meats are considered a valuable part of the human diet and a best source of B-group vitamins. Thus, investigations that measure the losses by cooking and bioaccessibilities of micronutrients are crucial to knowing the vitamin amounts in meats. The aim of this research was to investigate the content and loss of thiamine in meats by four different cooking practices, boiling, roasting, grilling, and frying, and to determine the bioaccessibility of thiamine in cooked meats by a simulated in vitro human gastrointestinal digestion system. High-performance liquid chromatography was used to detect the contents of thiamine in each raw and cooked meat. In raw meats, the measured thiamine amounts varied from 58.67 to 159 µg/100 g. After cooking, the amounts of thiamine ranged between 21 – 93 µg/100 g. While the lowest thiamine loss was determined in the boiled mutton thigh (8%), the highest loss was found in roasted veal thigh and mutton sleeve with 64%. The bioaccessibilities of thiamine in meats after digestion ranged from 12 to 83 µg/100 g. The highest thiamine bioaccessibility was in the grilled veal chop with 91%, while the lowest bioaccessibility was found in the roasted mutton sleeve with 12%. The bioaccessibility of vitamins may be remarkably influenced by factors such as stability, pH of the gastrointestinal tract, and temperature. Determining the bioaccessibility of thiamine in meats after cooking and digestion is important for the correct evaluation of the daily intake values ??of these vitamins.
Keywords: Meats; Thiamine; Cooking loss; In vitro gastrointestinal digestion; HPLC